Policymakers and Policy Evolution of Scientific and Technological Resource Integration in China - Yonghui, Guo; Jie, Li (Journal of the knowledge economy, 2024)
The policy system is an important guarantee for promoting the integration of scientific and technological resources. In China, the evolution of the policy system for integrating scientific and technological resources can be divided into three stages. The first stage, from 1978 to 1998, was characterized by one-way policies that allowed military resources to be used for civil development. The second stage, from 1999 to 2006, focused on promoting policies that facilitated the sharing of civil-military resources. The current stage, which began in 2007 and continues to the present, is characterized by policies aimed at deepening the integration of military and civilian resources. Policy levels and the effectiveness of policies at each stage are analyzed using the content analysis method. Meanwhile, the main structure of policymakers is being studied. With the social analysis software UCINET 6.0, the cooperative network structure and the evolutionary characteristics of policymakers are analyzed. The research indicates that, despite ongoing improvements, there is still room for enhancement in the policy of science and technology resource integration in China. Despite the continuous expansion of the participation scale of policy subjects, there is a need to deepen cooperation. Finally, this study presents suggestions for enhancing the policy system of military-civilian science and technology collaborative innovation from the perspective of policy and policymakers. These suggestions aim to overcome the barriers related to property rights and standards in integrating science and technology resources, thereby facilitating the practical implementation of resource integration.